Disjointed Perspectives on Motherhood - Florescu, Catalina Florina (Lexington Books, 2013)
Disjointed Perspectives on Motherhood presents the accounts of mothers who have suffered a major physical and/or psychically traumatic accident, and, as a consequence, their minds and bodies have been drastically changed. They live under the pressure of having discovered the alter ego of their traumatized personality, and now, distressed, cannot embrace their unconditional maternal love. Instead, they enter into a phase where they face the challenge of revealing who they are as persons before accepting or motivating themselves as mothers. The mothers presented in this volume also seem to have another thing in common: their transnational, fluid, female identity as they enter into an imaginary dialog that transcends geographical and temporal perspectives on womanhood and motherhood. This collection introduces and analyzes recurrent words that define a woman's body and mind today: fear, competition, motherhood and career rights, selfishness, ambition, destruction, distance, and identity. By using unprecedented comparative critical approaches such as phenomenological, medical, feminist, and re-enchantinent theories, and by analyzing works from literature, cinema, and visual arts, this collection attempts to reestablish and redefine a canonical concept with the intention to revitalize an otherwise taken-for-granted image and role.